A Graphical Environment for the Semantic Validation of a Plan Execution Language (2009)
This paper presents PLEXIL5, PLEXIL's formal interacting visual environment, a graphical environment providing an user-friendly interface to the formal operational semantics of PLEXIL. PLEXIL is a synchronous plan execution language developed by NASA to support autonomous space operations. PLEXIL5 serves as a testbed for designers, developers and users of PLEXIL's executive system to validate, maintain, and debug the implementation of the system against the formal semantics of the language. The executable formal semantics of PLEXIL is an executable rewriting logic theory in Maude's language.